Building on borrowed time: rising seas and failing infrastructure in Semarang - Ley, Lukas (University of Minnesota Press, 2021)
"A timely ethnography of how Indonesia's coastal dwellers inhabit the "chronic present" of a slow-motion natural disaster"--